Hierarchical Reputation Consensus Model for VANET - Ruilong Chen; Yepeng Guan (IEEE Access)
The vehicular ad hoc network (VANET) enables vehicles to disseminate messages to improve traffic safety and efficiency. However, the task of enabling consensus through synchronous communication among them remains a challenging problem due to the high mobility of vehicles. This prompts the need for a consensus model suitable for VANETs. Thus, A hierarchical reputation consensus model for VANET has been proposed. The model dynamically partitions consensus groups based on vehicles’ global reputation, which restricts malicious nodes from participating in consensus to improve consensus efficiency. Secondly, an improved event reliability assessment mechanism is introduced into the reputation model to detect the authenticity of the events and mitigate the fabrication of false events. Finally, a hierarchical directed gossip consensus model based on directed acyclic graph (DAG) called as HDGgraph has been proposed. It is aimed at addressing the challenge of achieving consensus when vehicle communication synchronization cannot be guaranteed. In HDGgraph, vehicles can construct a DAG locally and implement virtual voting to achieve local consensus, which can reduce system communication overhead and significantly improve consensus efficiency. Experimental results demonstrate that our proposed approach outperforms some state-of-the-art methods in terms of performance.